Zeitoun Faculty Guide - Kansas State University, K-State First (Kansas State University. K-State First., 2011)
Developed for instructors, this guide to "Zeitoun" by Dave Eggers includes discussion questions and recommended books and films.
Keywords: Zeitoun; Guide; First-year experience program; Engagement; Common reading program; Brochures